Bleaching gel volume influences hydrogen peroxide diffusion, inflammation, and the presence of nitric oxide in the pulp tissue: in vitro and in vivo model - de ALCÂNTARA, Sibele [UNESP]; Benetti, Francine; da SILVA, Lívia Maria Alves Valentim [UNESP]; Machado, Nathália Evelyn da Silva [UNESP]; Silva, Isabela Joane Prado [UNESP]; Esteves, Lara Maria Bueno [UNESP]; Ervolino, Edilson [UNESP]; Cintra, Luciano Tavares Angelo [UNESP]; Briso, André Luiz Fraga [UNESP] (FapUNIFESP (SciELO), 2023)
Objective: To assess whether bleaching gel volume influences chromatic changes, hydrogen peroxide (HP) diffusion, inflammation, and oxidative stress in the pulp tissue. Methodology: A total of 60 bovine teeth were divided into four groups, according to bleaching gel volume (n=15): without gel (WG); V30 (30 µL of 35% HP); V60 (60 µL); and V120 (120 μL). HP diffusion analysis was performed in the first session (T1). Chromatic changes (ΔE, ΔE00, and WID) were assessed after the first (T1), second (T2), third (T3) sessions, and 15 d (T4) after the end of treatment. Moreover, 20 rats were randomly divided into four groups (n=10) and their upper first molars were treated with different gel volumes: control (no treatment); V2 (2 μL of 17.5% HP); V4 (4 μL); and V8 (8 μL). After 24 h, rats were euthanized and the specimens processed for histological and immunohistochemical (nitric oxide synthase) evaluation. Data were analyzed using the Wilcoxon and Mann-Whitney tests (p<0.05). Results: In vitro (bovine teeth), chromatic changes were not influenced by bleaching gel volume, showing similar values in all groups and sessions, except for the control group (p<0.05). The V120 group had the highest HP diffusion values (p<0.05). In vivo (pulp tissue), the V4 and V8 groups showed the highest inflammatory infiltrate in the pulp and significant oxidative stress (p<0.05). Conclusion: The adverse effects on the dental pulp related to HP diffusion, pulp inflammation, and oxidative stress depend on bleaching gel volume, while the bleaching effect is not proportional to the volume used.
Keywords: Dosage; Hydrogen peroxide; Nitric oxide; Oxidative stress; Tooth bleaching